Rebuilding Higher Educational Institutions in Nigeria: Edeh's Responsive Approach - Christian Nwakanma PhD (Knowledgeable Research A Multidisciplinary Journal, 2025)
This study is on rebuilding higher educational institutions in Nigeria: Edeh''s responsive approach. Descriptive survey research design was used for this study. Between 1990 and 1999 Edeh saw Nigerian higher educational institutions in a state of quagmire due to poor funding, frequent flight of lecturers to Diasporas countries of the world in search of rewarding academic jobs, cultism, rape, thuggery, inadequate facilities, dilapidated equipment and facilities among others. These issues and problems prompted Edeh to establish private higher educational institutions where cultism, rape, stealing, examinations malpractices, strikes, frauds would be forbidden. Two research questions were raised by the researcher as; what are the causes of inordinate attitudes in Nigerian educational system?, What are the issues retarding effective administration of higher educational institutions in Nigeria? Findings from this study revealed that inadequate administration of higher educational institutions is the major causes of rape, cultism, inadequate infrastructural facilities, under funding in higher educational institutions in Nigeria.  Findings of this study revealed that rape, cultism, smoking, underfunding, inadequate infrastructural facilities, incessant strikes, were the issues / problems retarding effective administration of higher educational institutions in Nigeria. It was recommended from this study that higher educational institutions heads should buy Edehs educational ideas to stop rape, cultism, stealing, underfunding, inadequate infrastructural facilities in Nigerian higher educational institutions through effective students’ enlightenment campaigns, conferences, symposiums, team building to ensure sanity in higher educational institutions in Nigeria.  It was also, recommended from this study that government should provide facilities, equipment, effective funding in public higher educational institutions in Nigeria. This would reduce influx of dilapidated building and poor staff remunerations in public private universities in Nigeria. It was also, suggested in this study that proprietors of  private higher educational institutions in Nigeria should embrace positive change through provision of needed facilities, equipment and eradication of rape, cultism, stealing in private universities in Nigeria